Automatic extension (SMART X) / Muhammad Ibrahim Ismail, Noor Farhana Kamaluddin and Norfarahin Mohd Yusoff - Ismail, Muhammad Ibrahim; Kamaluddin, Noor Farhana; Mohd Yusoff, Norfarahin Rinti (2015)
Automatic extension or Smart X is functions to help busy people when doing their chores by switch off the electronic devices when they are busy or forget to. This device can off the switch by using motion movement where when they are not near in a certain distance with the electronic devices, the switch will automatically switch off after 1 minute there detected no movement, it also can be set by using timer, where people can set a certain time for their device to switch off so that they can save more electricity expenses. By using the timer, people will be reminded by the sound of buzzer for the last 10 minutes and last 1 minute, then the user can input again the time required or the switch will be turn off.